IMPLEMENTATION OF ISLAMIC BUSINESS ETHICS IN E-COMMERCE MARKETING IN THE SHOPEE MARKETPLACE - Misnawati, Misnawati; Firman Setiawan (I-Finance Journal, 2024)
This descriptive qualitative research aims to describe how Islamic business ethics influence marketing practices in the Shopee marketplace. This research uses primary and secondary data methods. Informants in this research include sellers at the Shopee Marketplace in the city of Sampang and outside the city of Sampang. Using an approach with qualitative research methods. To check and test data validity techniques, use the Triangulation method. Data analysis in this research was carried out through the stages of data reduction, data presentation, and drawing conclusions as the final goal. The research results show that in Islamic Business Ethics in marketing on the Shopee Marketplace it is important to prevent practices of manipulation, intimidation or immoral behavior towards buyers which include: Unity, Balance, Free Will, Responsibility ( Responsibility), and Truth (Truth) The conclusion in this research is that the implementation of Islamic Business Ethics in marketing activities at the Shopee Marketplace has not been fully implemented in its entirety. The importance of applying Islamic Ethics to marketing interactions with interactions with sellers in the marketing process to provide a deeper understanding.